Pore‐forming process in dehydration of metakaolin‐based geopolymer - Yaru Yang; Thi‐Chau‐Duyen Le; Isamu Kudo; Thi‐Mai‐Dung Do; Koichi Niihara; Hisayuki Suematsu; Gordon Thorogood (International Journal of Ceramic Engineering & Science, 2021)
Abstract The geopolymer catalyst supports utilized in the nuclear waste containers for the Fukushima Daiichi Nuclear Power Station will be required to have high porosity and durability. This work presents the synthesis of a potassium and metakaolin‐based geopolymer and its performance upon dehydration. During water content measurements of the samples, it was seen that in the demolded samples, the water content quickly decreased to less than 30% within 7 days, while the samples that had the cap removed from the container retained more than 50% of the water after 28 days. The pore size distribution of the samples that were post‐cured at different temperatures up to 28 days did not vary greatly with respect to the average pore size. We can infer that structurally stable pores were formed in the first 4 days and were not affected by the post‐curing rate, which may be related to rheological properties and the drainage path of water or hydrogen gas during post‐curing.